Best practices for cystometric evaluation of lower urinary tract function in muriform rodents. Issue 6 (8th June 2020) - Fraser, Matthew O.; Smith, Phillip P.; Sullivan, Maryrose P.; Bjorling, Dale E.; Campeau, Lysanne; Andersson, Karl‐Erik; Yoshiyama, Mitsuharu
Abstract: Aims: Rodent cystometry has provided valuable insights into the impact of the disease, injury, and aging on the cellular and molecular pathways, neurologic processes, and biomechanics of lower urinary tract function. The purpose of this white paper is to highlight the benefits and shortcomings of different experimental methods and strategies and to provide guidance on the proper interpretation of results. Methods: Literature search, selection of articles, and conclusions based on discussions among a panel of workers in the field. Results: A range of cystometric tests and techniques used to explore biological phenomena relevant to the lower urinary tract are described, the advantages and disadvantages of various experimental conditions are discussed, and guidance on the practical aspects of experimental execution and proper interpretation of results are provided. Conclusions: Cystometric evaluation of rodents comprises an extensive collection of functional tests that can be performed under a variety of experimental conditions. Decisions regarding which approaches to choose should be determined by the specific questions to be addressed and implementation of the test should follow standardized procedures.